Quantitative 7-Tesla Imaging of Cortical Myelin Changes in Early Multiple Sclerosis - Barletta, Valeria; Herranz, Elena; Treaba, Constantina A.; Mehndiratta, Ambica; Ouellette, Russell; Mangeat, Gabriel; Granberg, Tobias; Sloane, Jacob A.; Klawiter, Eric C.; Cohen-Adad, Julien; Mainero, Caterina (Frontiers in Neurology, 2021)
Cortical demyelination occurs early in multiple sclerosis (MS) and relates to disease outcome. Brain cortex has endogenous propensity for remyelination as proven from histopathology study. In this study, we aimed at characterizing cortical microstructural abnormalities related to myelin content by applying a novel quantitative MRI technique in early MS. A Combined Myelin Estimation (CME) cortical map was obtained from quantitative 7-Tesla (7T) T2* and T1 acquisitions in 25 patients with early MS and 19 healthy volunteers. Cortical lesions in MS patients were classified based on their myelin content by comparison with CME values in healthy controls as demyelinated, partially demyelinated or non-demyelinated. At follow-up, we registered changes in cortical lesions as increased, decreased or stable CME. Vertex-wise analysis compared cortical CME in the normal-appearing cortex in 25 MS patients versus 19 healthy controls at baseline and investigated longitudinal changes at 1 year in 10 MS patients. Measurements from the neurite orientation dispersion and density imaging (NODDI) diffusion model were obtained to account for cortical neurite/dendrite loss at baseline and follow-up. Finally, CME maps were correlated to clinical metrics. CME was overall low in cortical lesions (p=0.03) and several normal-appearing cortical areas (p<0.05) in the absence of NODDI abnormalities. Individual cortical lesion analysis revealed, however, heterogeneous CME patterns from extensive to partial or absent demyelination. At follow-up, CME overall decreased in cortical lesions and non-lesioned cortex, with few areas showing an increase (p<0.05). Cortical CME maps correlated with processing speed in several areas across the cortex. In conclusion, CME allows to detect cortical microstructural changes related to coexisting demyelination and remyelination since the early phases of MS, shows to be more sensitive than NODDI and relates to cognitive performance.